Advancing the debate on hotel employees’ environmental psychology by promoting energy-saving behavior in a corporate social responsibility framework - Yang, Long; Cherian, Jacob; Sial, Muhammad Safdar; Samad, Sarminah; Yu, Jongsik; Kim, Youngbae; Han, Heesup (Frontiers in Psychology, 2022)
Considering the vulnerable climatic conditions in most parts of the planet, a successful transition toward a carbon-free future is a critical challenge worldwide. In this respect, around 35% of the world’s total greenhouse gas emission (GHG) is associated with the power sector (especially electrical energy). To this end, a vast of electrical energy has been used by the people in buildings. Specifically, a significant amount of energy in buildings is used for heating, cooling, and ventilation. While the available literature highlights the importance of neat, clean, and green electrical energy for the decarbonization of society, a critical gap exists in such literature. That is, most of the literature under this stream deals with the supply side (production) of electrical energy, while the demand side (consumption at an individual level) was neglected. To bridge this critical knowledge gap, this study investigates how the CSR engagement of a hotel organization can promote the energy-related pro-environmental behavior (ERPEB) among the employees with the intervening effect of employees’ environmental commitment (EMEC) and Green intrinsic motivation (GRIM). Further, the conditional indirect role of altruistic values was also tested in this study. The data were collected from different hotel employees in Pakistan with the help of a self-administered questionnaire. We tested the hypothesized relationship through structural equation modeling (SEM). The results confirmed that CSR can be a potential motivator to impact the ERPEB of employees, while EMEC and GRIM mediated this relationship significantly. The findings of this study also confirmed the conditional indirect role of altruistic values. These findings offer various theoretical and practical contributions which are conversed in detail.